2011
DOI: 10.1007/s10877-011-9309-x
|View full text |Cite
|
Sign up to set email alerts
|

Bi-spectral index, entropy and predicted plasma propofol concentrations with target controlled infusions in Indian patients

Abstract: The target plasma propofol concentrations required to produce unconsciousness and loss of response to painful stimuli in Indian patients have been estimated. Also, the relations between target plasma concentration and objective measures of different levels of anaesthesia have been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Other studies have demonstrated that BIS values correlate well with increasing propofol dosages, even if BIS levels at induction are lower than expected. 25 In 2013, Martín-Mateos and colleagues showed that BIS values fluctuate around an index of 50 and that this fluctuation varies among patients. 26 In our study, approximately 50% of patients demonstrated low BIS values, and in five of these patients, the EEG showed a burst suppression pattern, which signifies overly deep anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that BIS values correlate well with increasing propofol dosages, even if BIS levels at induction are lower than expected. 25 In 2013, Martín-Mateos and colleagues showed that BIS values fluctuate around an index of 50 and that this fluctuation varies among patients. 26 In our study, approximately 50% of patients demonstrated low BIS values, and in five of these patients, the EEG showed a burst suppression pattern, which signifies overly deep anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Puri et al . [ 26 ] in their study observed an effective concentration (EC 50 ) and EC 95 of plasma propofol as 2.3 μg/ml and 2.8 μg/ml, respectively, for loss of response to verbal command without fentanyl in patients who went through elective surgeries. The data give supportive evidence on propofol pharmacokinetics in Indian patients.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the example of inter-racial variability: a simulator that has perfect repeatability when running a propofol-based conscious sedation scenario in countries with predominantly Caucasian populations and also in India would actually be undesirable because, on average, Indian patients are significantly more sensitive to propofol than are Caucasian patients. 9 Patient variability calls for patient-centered simulation, 7 which is still in its infancy but has the potential to accelerate the current trend toward adoption and routine practice of patient-centered medicine.…”
Section: Variability Vs Repeatabilitymentioning
confidence: 99%